[INVITED] Biomimetic photonic structures for optical sensing. (January 2019) - Martín-Palma, Raúl J.; Kolle, Mathias
Highlights: A selection of optical sensors, which have been developed using biomimetic photonic structures is reviewed. We discuss how biomimetic-based design strategies have led to the successful fabrication of different sensors. Types of sensors: Infrared, chemical, mechanical. Sensors for aerospace applications and robotics. Abstract: This perspective reviews a selection of optical sensors, which have been developed using biomimetic photonic structures. In particular, we discuss how biomimetic-based design strategies have led to the successful fabrication of infrared, chemical, and mechanical sensors, as well as sensors for aerospace applications and robotics.